Dialkylthio benzo[1, 2-b:4, 5-b′]difuran polymer for efficient organic photovoltaics with solvent treatment in active layers. (August 2016) - Yu, Jiangsheng; Luo, Guoping; Bian, Linyi; Zhou, Baojing; Yin, Xinxing; Xu, Zhongsheng; Zhang, Fujun; Deng, Ping; Wu, Hongbin; Tang, Weihua
Abstract: The facile synthesis of dialkylthio substituted benzo[1, 2- b :4, 5- b′ ]difuran unit via a straightforward palladium-catalyzed carbon–sulfur bond formation reaction is reported. A novel donor–acceptor alternating copolymer was further developed by Stille coupling. The optical and electrochemical properties of the polymer have been carefully studied. The photovoltaic performance by blending the copolymer with [6, 6]-phenyl-C71 -butyric acid methyl ester were explored in both conventional and inverted solar cell devices. Solvent additive and vapor treatment exhibit positive effects on the device performance. The best devices delivered a power conversion efficiency of 5.48%, with an active layer processed from chloroform solutions with 1, 8-diiodooctane (3%) and 30 s tetrahydrofuran vapor treatment. Highlights: The facile synthesis of dialkylthiobenzo[1, 2- b :4, 5- b' ]difuran. The electrochemical characterization of polymerPBDFs-DTBTff . The enhancement of solvent additive and THF vapor treatment on device performance. The demonstration of the highest PCE of 5.48% forPBDFs-DTBTff based devices.